Derivative (5;19)(p10;q10): A rare but recurrent whole‐arm translocation in acute myeloid leukemia. Issue 2 (27th December 2012) - Manabe, Masahiro; Takakuwa, Teruhito; Nakano, Hirofumi; Harada, Naonori; Okamoto, Shuichiro; Aoyama, Yasutaka; Kumura, Takeo; Ohta, Tadanobu; Furukawa, Yoshio; Matsuda, Mitsuhiro; Mugitani, Atsuko
Abstract A previous study of cases of myelodysplastic syndrome harboring der(5;19)(p10;q10) found that they displayed common characteristics including predominance in elderly men, dysplasia involving three hematopoietic lineages and CD7 expression in blasts. However, the whole‐arm translocation der(5;19)(p10;q10) has not been fully analyzed because of its rarity. In this study we used flow cytometry to evaluate the immunophenotype of two patients' bone marrow mononuclear cells. Both patients had involved der(5;19)(p10;q10) in their karyotype analyzed by standard G‐banding technique. Both patients had the CD7+ and CD41+ phenotype, and the CD41 positivity suggested that the myeloid neoplasms involving der(5;19)(p10;q10) were of megakaryoblastic origin. The der(5;19)(p10;q10) abnormality is associated with unique characteristics of the immunophenotype. We address the clinical, immunophenotypic and morphological aspects of hematological malignancy involving der(5;19)(p10;q10), along with a review of the literature.